Insights into the Transmission, Host Range, Genomics, Vaccination, and Current Epidemiology of the Monkeypox Virus - Yusha Araf; Jannatul Ferdous Nipa; Sabekun Naher; Sumaiya Tasnim Maliha; Hasanur Rahman; Kazi Ifthi Arafat; Mohammad Raguib Munif; Md Jamal Uddin; Nurejunnati Jeba; Sukumar Saha; Jingbo Zhai; S. M. Nazmul Hasan; et al. (Veterinary Medicine International)
This review delves into the historical context, current epidemiological landscape, genomics, and pathobiology of monkeypox virus (MPXV). Furthermore, it elucidates the present vaccination status and strategies to curb the spread of monkeypox. Monkeypox, caused by the Orthopoxvirus known as MPXV, is a zoonotic ailment. MPXV can be transmitted from person to person through respiratory droplets during prolonged face-to-face interactions. While many cases of monkeypox are self-limiting, vulnerable groups such as young children, pregnant women, and immunocompromised individuals may experience severe manifestations. Diagnosis predominantly relies on clinical presentations, complemented by laboratory techniques like RT-PCR. Although treatment is often not required, severe cases necessitate antiviral medications like tecovirimat, cidofovir, and brincidofovir. Vaccination, particularly using the smallpox vaccine, has proven instrumental in outbreak control, exhibiting an efficacy of at least 85% against mpox as evidenced by data from Africa. Mitigating transmission requires measures like wearing surgical masks, adequately covering skin lesions, and avoiding handling wild animals.